2022
DOI: 10.1002/chem.202201816
|View full text |Cite
|
Sign up to set email alerts
|

Entropy‐Induced Selectivity Switch in Gold Catalysis: Fast Access to Indolo[1,2‐a]quinolines

Abstract: New N-heterocyclic compounds for organic functional materials and their efficient syntheses are highly demanded. A surprising entropy-induced selectivity switch in the gold-catalyzed intramolecular hydroarylation of 2-ethynyl N-aryl indoles was found and its exploitation led to straightforward syntheses of indolo[1,2-a]quinolines. Experimental and computational mechanistic investigations gave insight into this uncommon selectivity phenomenon and into the special reactivity of the indolo[1,2-a]quinolines. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 125 publications
1
14
0
Order By: Relevance
“…This provides an explanation for the high instability against oxygen for BBPQ‐1 , where the combination of a high lying HOMO and a non‐blocked pyrrole carbon results in a high reactivity of this position towards oxygen leading to decomposition. This aspect correlates with observations in our preceding work, where related molecules show a similar reactivity on the unprotected pyrrole carbon, when the HOMO is relatively high in comparison to more stable molecules [5] . Although BBPI‐1 has an unprotected pyrrole carbon similar to BBPQ‐1 , the HOMO energy is calculated to be 0.36 eV lower.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This provides an explanation for the high instability against oxygen for BBPQ‐1 , where the combination of a high lying HOMO and a non‐blocked pyrrole carbon results in a high reactivity of this position towards oxygen leading to decomposition. This aspect correlates with observations in our preceding work, where related molecules show a similar reactivity on the unprotected pyrrole carbon, when the HOMO is relatively high in comparison to more stable molecules [5] . Although BBPI‐1 has an unprotected pyrrole carbon similar to BBPQ‐1 , the HOMO energy is calculated to be 0.36 eV lower.…”
Section: Resultssupporting
confidence: 89%
“…In this work we exclusively used CD 2 Cl 2 in order to prevent overlapping of the product signals with the residual signal of undeuterated solvent. In preceding work [5] we demonstrated that the related monodirectionally prepared compounds tend to be protonated very easily when using non‐purified CDCl 3 which contains traces of acid; a small shift in some 1 H NMR signals could be observed, which was not the case when using CDCl 3 filtered through aluminum oxide.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Until recently, appropriate starting materials necessary for the bidirectional PSR were difficult or impossible to synthesize. Fortunately, we lately developed a versatile gold-catalyzed [51][52][53][54][55][56][57][58][59] method for the building of benzodipyrroles and therein showed the example of bis(2-aminophenyl)-substituted benzodipyrrole 1 (Scheme 2). 60 This substrate is accessible starting from 1,4-diiodo-2,5-dimethoxybenzene in a straightforward four step synthesis and should be suitable for the synthesis of BBPQs via the PSR.…”
Section: Reaction Discovery and Optimizationmentioning
confidence: 99%
“…In particular, 6-alkyl-12-formyl-5,6-dihydroindolo­[2,1- a ]­isoquinolines, the 3-formylindole derivatives, were also shown to possess inhibitory activity toward human mammary carcinoma cells (Figure b) . In addition, indolo­[1,2- a ]­quinolines bearing combined scaffolds of indoles and quinolines were demonstrated to exhibit applications in organic materials such as organic semiconductors and solar cell photosensitizers (Figure c). Though having been reported, synthetic approaches to construct indolo­[1,2- a ]­quinolines are rather limited . A Pd-catalyzed annulation of strained alkenes followed by a retro-Diels–Alder reaction was developed by Lautens and co-workers to prepare the indolo­[1,2- a ]­quinoline framework (Scheme a).…”
Section: Introductionmentioning
confidence: 99%